#### Answer

See the picture below.

#### Work Step by Step

By calculating the values of $f(x)=2x^2-1$ (with blue) and $g(x)=x^2$ (with red) we can see that the following equation is true: $2g(x)-1=f(x)$
In order to graph the parent function , here is the table of values:
$g(-2)=-2^2=4$
$g(-1)=-1^2=1$
$g(0)=0^2=0$
$g(1)=1^2=1$
$g(2)=2^2=4$
Therefore the graph of $f(x)$ is exactly the same as the graph of $g(x)=x^2$ but is wider (is stretched vertically by a factor of 2) and is translated 1 unit down.